STUDY ON THE USE OF PLIOMETRIC EXERCISES IN THE SPECIFIC - Maria Liliana MIRCICĂ; Cătălin PĂUNESCU; Gabriel PIŢIGOI; Silviu PETRESCU (Universitaria Publishing House, Craiova, 2018)
The concept of the method used for this application and carried out on a sample of Taekwondo athletes is trying to identify the adequate solution by simultaneously considering two criteria: the attribute of significance of the motricity investigation and the feature of practicality - in the sense of achieving an acceptable level of reliability and adequacy of the data while using a noninvasive device, which is also as less obtrusive as possible to the subjects. The study was conducted on 8 students, members of the taekwondo (TKD) team, of the Carol Davila University of Medicine and Pharmacy, with a competitive experience of 10 to 12 years. The Jump Pliometry assessment in anaerobic effort was performed using the Myotest PRO device. Two tests were performed, an initial one to determine the stadium level for jump pliometry, and a final test to determine the level of progress. The main objectives pursued by this test are: to measure the contractile and inter-muscular muscle coordination in the lower limbs and the values provided information on the quality of the jump that influences the sport performance. As a conclusion, by applying a centralized training program including pliometric exercises even in the specific part, significant changes in expansion, contact time, response and distribution of the load can be generated in the lower limbs.